Pendampingan Bantuan Sosial Terhadap Warga RT 14 Dusun Kadongdong Desa Kondangjaya Karawang (Studi Pengabdian Masyarakat Mahasiswi STIQ ZAD Cianjur) - Saputra, Adha; Fauziah, Ismi Latifah; Putri, Salsa Permata; Azzahra, Nada Aulia; Fathimah; Alfiani, Lutfi; Nursyamsiah Ardhiella; Tokan, Ayu Gorang; Afifah Nur (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2024)
This community service aims to help the food needs of the local community through social assistance programs implemented by group 01 KKN students of STIQ ZAD Cianjur which is materially sponsored with BAZNAS RI. This community service uses a field service method. Based on the results of the service, this social assistance program is carried out door to door for people who need assistance in the form of basic necessities. The benefits of this program are personal awakening with a high sense of socialization and increased welfare of the local community.